The metabolic underpinnings of temperature-dependent predation in a key marine predator - Csik, Samantha R.; DiFiore, Bartholomew P.; Kraskura, Krista; Hardison, Emily A.; Curtis, Joseph S.; Eliason, Erika J.; Stier, Adrian C. (Frontiers in Marine Science, 2023)
Introduction Changes in temperature can fundamentally transform how species interact, causing wholesale shifts in ecosystem dynamics and stability. Yet we still have a limited understanding of how temperature-dependence in physiology drives temperature-dependence in species-interactions. For predator-prey interactions, theory predicts that increases in temperature drive increases in metabolism and that animals respond to this increased energy expenditure by ramping up their food consumption to meet their metabolic demand. However, if consumption does not increase as rapidly with temperature as metabolism, increases in temperature can ultimately cause a reduction in consumer fitness and biomass via starvation. Methods Here we test the hypothesis that increases in temperature cause more rapid increases in metabolism than increases in consumption using the California spiny lobster (Panulirus interruptus) as a model system. We acclimated individual lobsters to temperatures they experience sacross their biogeographic range (11, 16, 21, or 26°C), then measured whether lobster consumption rates are able to meet the increased metabolic demands of rising temperatures. Results and discussion We show positive effects of temperature on metabolism and predation, but in contrast to our hypothesis, rising temperature caused lobster consumption rates to increase at a faster rate than increases in metabolic demand, suggesting that for the mid-range of temperatures, lobsters are capable of ramping up consumption rates to increase their caloric demand. However, at the extreme ends of the simulated temperatures, lobster biology broke down. At the coldest temperature, lobsters had almost no metabolic activity and at the highest temperature, 33% of lobsters died. Our results suggest that temperature plays a key role in driving the geographic range of spiny lobsters and that spatial and temporal shifts in temperature can play a critical role in driving the strength of species interactions for a key predator in temperate reef ecosystems.